2017
DOI: 10.1038/nature21722
|View full text |Cite|
|
Sign up to set email alerts
|

Myt1l safeguards neuronal identity by actively repressing many non-neuronal fates

Abstract: Normal differentiation and induced reprogramming require the activation of target cell programs and silencing of donor cell programs. In reprogramming, the same factors are often used to reprogram many different donor cell types. As most developmental repressors, such as RE1-silencing transcription factor (REST) and Groucho (also known as TLE), are considered lineage-specific repressors, it remains unclear how identical combinations of transcription factors can silence so many different donor programs. Distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
271
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 196 publications
(288 citation statements)
references
References 51 publications
12
271
5
Order By: Relevance
“…Since both Ascl1 and Myod1 (a myogenic bHLH TF) bind a common E-box sequence (CAGCTG) (Castro et al, 2011; Fong et al, 2015), we speculate that the strong over expression of Ascl1 led to the initiation of an off-target myogenic program that is not normally observed in a more tightly controlled endogenous environment. This is also consistent with our recent finding that Myt1l represses non-neuronal fates, including myogenic genes, suggesting potential synergy between Ascl1 and Myt1l (Mall et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
“…Since both Ascl1 and Myod1 (a myogenic bHLH TF) bind a common E-box sequence (CAGCTG) (Castro et al, 2011; Fong et al, 2015), we speculate that the strong over expression of Ascl1 led to the initiation of an off-target myogenic program that is not normally observed in a more tightly controlled endogenous environment. This is also consistent with our recent finding that Myt1l represses non-neuronal fates, including myogenic genes, suggesting potential synergy between Ascl1 and Myt1l (Mall et al, 2017). …”
Section: Discussionsupporting
confidence: 93%
“…Although Myt1l bound to similar sites in both MEFs and neurons, it alone was not sufficient to elicit neuronal reprogramming. Structure-function experiments suggested that Myt1l acts as a transcriptional repressor, which is consistent with its interaction with Sin3B (Mall et al, 2017). Transcriptomic data suggest that many genes and possibly somatic expression programmes, including genes representing a fibroblast signature, are downregulated by Myt1l, and that neural genes are impoverished in Myt1l binding sites.…”
Section: Programming Adult Nscsmentioning
confidence: 56%
“…A recent study on iPS cell reprogramming suggested that the reprogramming factors themselves initially bind and decommission fibroblast enhancers and gradually activate pluripotency enhancers [70]. Investigating the iN cell reprogramming mechanism, we found that Myt1l, one of the three reprogramming factors, appears to be dedicated to suppress the fibroblast and many other non-neuronal programs whereas activation of the neuronal program is accomplished by the “on target pioneer” factor Ascl1 [69, 79]. Therefore, repressing alternative cell fates along with concomitant induction of cell type specific programs enable faithful and efficient binary decisions during cell fate reprogramming.…”
Section: Donor Program Repressionmentioning
confidence: 96%